COMPREHENSIVE APPROACH AS A METHOD OF OPTIMIZATION METHODS AND TECHNIQUES OF TEACHING (Pedagogy of Higher and Secondary Education, 2022)
In the article the integrated approach to the means of improving teaching methods and modes is regarded (general practical aspect).